A cross-sectional study among defaulters of DOTS under RNTCP in tuberculosis units of Solapur city - D. Gosavi, Anand; A. Nandimath, Viresh; K. Mangulikar, Suresh (International Journal Of Community Medicine And Public Health, 2019)
Background: Tuberculosis (TB) is a specific infectious disease caused by mycobacterium tuberculosis affecting pulmonary and extra-pulmonary organs. Default is one of the unfavorable outcomes for patients on DOTS and represents an important challenge for the control programme. Inadequate treatment adherence is considered as a potential cause of drug resistance. This study was conducted ascertain causes of defaults & to study socio-demographic corelates of defaulters. Methods: A cross-sectional study was conducted from 1st January 2014 to 31st December 2014. All default patients registered from 1st January 2014 to 31st December 2014 under RNTCP in both Tuberculosis Units of Municipal Corporation are considered for this study. Results: Total 104 cases of defaulters were registered under RNTCP in both TB units; 83 (79.8%) defaulters were males and remaining 21 (21.2%) were females and difference was statistically significant. Side effects of DOTS drugs were the most common reason of defaulting the treatment. Default of DOTS was significantly associated with socioeconomic status, educational status, addiction, religion and marital status of the patients. Conclusions: Poverty has effect on illness and completion of treatment.